Analisis Penggunaan Safety Harness di Ketinggian dalam Menjamin Keselamatan Kerja di PT. XYZ - Rangga Wiradarma (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study analyzes the use of safety harnesses in ensuring workplace safety at PT. XYZ, focusing on their role in preventing accidents during high-altitude work. The research employs the Job Safety Analysis (JSA) method to identify potential hazards and evaluate risk control measures. Data from 2021 to 2024 reveal a significant correlation workplace accidents with injuries ranging from minor to severe. The findings underscore the importance of strict adherence to safety regulations, proper training, and routine equipment inspections. The study concludes that consistent use of safety harnesses, aligned with national and industry standards, can significantly reduce accident rates and enhance worker safety.